SOCIAL STUDIES TEACHERS' STRATEGIES IN FOSTERING STUDENTS' SOCIAL ATTITUDES AT SDN 81 TERNATE CITY: STRATEGI GURU MATA PELAJARAN IPS DALAM MENUMBUHKAN SIKAP SOSIAL SISWA DI SDN 81 KOTA TERNATE - Amir Rifin; Rustam Hasim; Mohtar Kamisi (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This study aims to identify and analyze the strategies implemented by social studies teachers in fostering students' social attitudes at SDN 81 Ternate City. This study uses a qualitative approach with a descriptive method. Data were obtained through observation, interviews, and documentation of social studies teachers, students, and other related parties at the school. The results of the study indicate that social studies teachers at SDN 81 Ternate City use various strategies to foster students' social attitudes, including through group discussion approaches, case studies, educational games, and giving assignments that prioritize cooperation. In addition, the application of social values ​​in learning activities is also an important factor in instilling social attitudes among students. This study concludes that the active role of teachers in designing learning that involves social interaction between students is very influential in forming positive social attitudes. Therefore, it is hoped that teachers can continue to develop more creative and innovative strategies in building students' social attitudes in the future.